Identifying gaps in technology-based intervention prevention programs and ways to foster learning and engagement with parents using serious games - Wright, Michelle F.; Azar, Sandra T. (Frontiers in Public Health, 2025)
Some researchers have implemented technologies to help overcome the barriers to reducing childhood injuries. Many of these technology-based injury prevention programs rely on individually tailored, written feedback to help improve parents’ knowledge of home safety. Serious game technologies might further aid in developing injury prevention programs that are adaptive to the unique characteristics of parents. The purpose of this paper is to review these early efforts and propose serious game technology as a critical future direction of injury prevention programs with parents. The paper begins by discussing the barriers associated with reducing childhood injuries and engaging in injury prevention programs. Studies on injury prevention programs using technology to teach parents injury prevention skills are then described. Serious game technologies are proposed as having the potential to reduce injuries and barriers. The paper concludes with describing Home Safety Hero, an injury prevention program, and preliminary data from parents’ game play.